Occurrence of Writing Tremor in Patients With Scans Without Evidence of Dopaminergic Deficit. Issue 4 (24th December 2015) - Schirinzi, Tommaso; Imbriani, Paola; D'Elia, Alessio; Bentivoglio, Anna Rita; Pisani, Antonio
Abstract: Asymmetric rest tremor is one of the main features of patients diagnosed with scans without evidence of dopaminergic deficit (SWEDD). Clinical and neurophysiological evidence suggests a dystonic origin of this tremor, although the underlying pathophysiology is still unclear. Dystonic tremor has a great tendency to vary with different postures or voluntary motor tasks. Here, we performed a phenomenological analysis of tremor in 14 patients with normal scans and in 14 tremor‐dominant Parkinson's disease (PD) patients by assessing the presence of writing tremor. The Wilcoxon‐Mann‐Whitney's test revealed that patients with normal scans exhibit writing tremor more frequently, regardless of the side mostly affected by motor disturbances in handwriting ( P < 0.01) and drawing (right hand: P = 0.01; left hand: P < 0.05). Our findings show that patients with asymmetric rest tremor and normal scans, contrarily to PD patients, present more commonly action tremor during writing tasks. This feature may thus be helpful to distinguish the two conditions.